Biomechanical Testing of Unstable Slipped Capital Femoral Epiphysis Screw Fixation. Issue 5 (July 2015) - Schmitz, Matthew R.; Farnsworth, Christine L.; Doan, Joshua D.; Glaser, Diana A.; Scannell, Brian P.; Edmonds, Eric W.
<x xml:space="preserve">Abstract</x> Background: In a prior biomechanical study, 2-screw fixation of anatomically reduced slipped capital femoral epiphysis (SCFE) demonstrated marginally greater stability than single-screw fixation. However, the authors judged the benefits of a second screw to be minimal compared with the additional complication risk. A similar evaluation of fixation stability in unstable moderately displaced SCFE is performed. Methods: SCFE model: Transverse periosteal incision and epiphyseal separation from the metaphysis by leveraging in 25-month-old porcine femurs. Four groups were evaluated: pinned (3.5 mm cortex screws; Synthes, Monument, CO) with no displacement (1 screw=group N1; 2 screws=group N2) or with moderate posterior-inferior displacement of 50% of the epiphyseal diameter (1 screw=group D1; 2 screws=group D2). Biomechanical testing: Cyclical shear forces (40 to 200 N, 1 Hz) were applied along the physeal plane. Maximum load increased by 100 N every 500 cycles until failure (epiphyseal translation greater than one third the epiphyseal diameter). Force cycles (the sum of the maximum cycle loads) and number of cycles to failure were reported. Results: A sample from each D1 and D2 had fixation problems (D1, D2: n=4; N1, N2: n=5). One D1 failed through the femoral neck; all others failed through the epiphysis. The data showed nonsignificant trends of greater force cycles for nondisplaced over displaced (P=0.13) and for 2 screws over 1 (P=0.19). Number of cycles to failure showed similar trends, with no significant differences between nondisplaced and displaced (P=0.10) and screw number (P=0.13). Force cycles were significantly greater in the N2 group than in the D1 group. Conclusions: A trend toward higher force cycles to failure in nondisplaced and 2-screw groups was observed. Higher force cycles correspond to greater physeal stability and thus decreased risk for subsequent displacement. Within displacement groups, adding a second screw did not significantly increase stability. Reduction of displaced SCFE also did not significantly increase stability. Only the D1 and N2 groups were significantly different. Clinical Relevance: Nondisplaced SCFE does not require 2 screws. In situ fixation of displaced SCFE might be optimized with 2 screws.